Mitochondrial DNA reveals the natal origin of Caretta caretta (Testudines: Cheloniidae) stranded or bycaught along the Southwestern Adriatic coasts. Issue 1 (1st January 2017) - Splendiani, A.; Fioravanti, T.; Giovannotti, M.; Dâ€™Amore, A.; Furii, G.; Totaro, G.; Nisi Cerioni, P.; Lucchetti, A.; Caputo Barucchi, V.
Abstract: The Mediterranean Sea is an important regional management unit (RMU) for the conservation of the loggerhead turtle ( Caretta caretta ) because it hosts both nesting and foraging grounds for this species. In this study, attention was focused on an important foraging ground located on the southern Italian coast of the Adriatic Sea, the Gulf of Manfredonia. In this area, C. caretta is threatened by a high level of anthropogenic pressure, especially caused by fishing activities. To understand the genetic composition of the Southwestern Adriatic feeding ground and to highlight which rookeries could be the most impacted by human activities in this area, the mitochondrial haplotype of 239 individuals stranded or incidentally caught in fishing gears from 2008 to 2013 was determined. A mixed stock analysis (MSA) identified the Mediterranean rookeries as the most important contributors to this feeding ground, with contributions also from Atlantic rookeries of Florida and Gulf of Mexico. Finally, the identification of two â€œorphan haplotypesâ€ and the recovery of three hatchlings on the Vieste beach draw attention to the need for better identification and genetic characterisation of new nesting sites within the Mediterranean Basin.